KEPEMIMPINAN TRANSFORMASIONAL CAMAT DI KANTOR KECAMATAN SUNGAI TABUKAN KABUPATEN HULU SUNGAI UTARA - M. Ridha Anshari (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2021)
This research started from the writer's curiosity about the transformational leadership of the sub-district head at the Sungai Tabukan District Office, Hulu Sungai Utara Regency. The approach used is quantitative research methods collected through the distribution of previously prepared questionnaires. This type of research is explanatory research and aims to provide an explanation of why something happens or answer the question